2020
DOI: 10.3390/molecules25184051
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of a Cordyceps sinensis Mycelium Culture Extract (Cs-4) on Rodent Models of Allergic Rhinitis and Asthma

Abstract: Allergic rhinitis and asthma are common chronic allergic diseases of the respiratory tract, which are accompanied by immunoglobulin E (IgE)-mediated inflammation and the involvement of type 2 T helper cells, mast cells, and eosinophils. Cordyceps sinensis (Berk.) Sacc is a fungal parasite on the larva of Lepidoptera. It has been considered to be a health-promoting food and, also, one of the best-known herbal remedies for the treatment of airway diseases, such as asthma and lung inflammation. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In China, there is a long-term history of traditional Chinese medicine (TCM) use in the treatment of respiratory diseases including asthma [ 8 ]. A diversity of TCMs have been determined to have therapeutic potential for asthma, such as Cordyceps sinensis [ 9 ], Astragalus membranaceus [ 10 ], Carthamus tinctorius [ 11 ], Atractylodis rhizome [ 12 ], and Cimicifugae Rhizoma [ 13 ]. Dioscorea nipponica Makino (DNM) is a perennial twining herb that exhibits a variety of medicinal functions, such as anti-inflammation, antitussive, antitumor, antipain, panting-calming and phlegm-dispelling, immune regulation, and cardiovascular system protection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, there is a long-term history of traditional Chinese medicine (TCM) use in the treatment of respiratory diseases including asthma [ 8 ]. A diversity of TCMs have been determined to have therapeutic potential for asthma, such as Cordyceps sinensis [ 9 ], Astragalus membranaceus [ 10 ], Carthamus tinctorius [ 11 ], Atractylodis rhizome [ 12 ], and Cimicifugae Rhizoma [ 13 ]. Dioscorea nipponica Makino (DNM) is a perennial twining herb that exhibits a variety of medicinal functions, such as anti-inflammation, antitussive, antitumor, antipain, panting-calming and phlegm-dispelling, immune regulation, and cardiovascular system protection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IL‐4, a significant cytokine of up‐regulating IgE, IFN‐γ is an anti‐allergic factor of respiratory tract and biological antagonist of IL‐4 synthesis. In the development and activation of eosinophils, IL‐5 plays a critical function, increased survival time and is a significant marker in the delayed phase of hypersensitivity (Chen, Chan, et al., 2020; Piao et al., 2020; Wang et al., 2020). Airway hyper responsiveness requires IL‐5‐mediated eosinophil infiltration in the trachea (Chen, Chan, et al., 2020; Piao et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the development and activation of eosinophils, IL‐5 plays a critical function, increased survival time and is a significant marker in the delayed phase of hypersensitivity (Chen, Chan, et al., 2020; Piao et al., 2020; Wang et al., 2020). Airway hyper responsiveness requires IL‐5‐mediated eosinophil infiltration in the trachea (Chen, Chan, et al., 2020; Piao et al., 2019). The results of the current experimental study showed that IL‐5 and IL‐4 were significantly reduced by Ajwain oil and increased the IFN‐γ level.…”
Section: Discussionmentioning
confidence: 99%
“…Cs-4, an extract of Cordyceps mycelium culture, has long been used for its immunomodulatory action. It has recently been demonstrated that Cs-4 treatment can produce anti-inflammatory effects in allergic rhinitis and asthma in rodent models [15]. CE, which is a health product based on traditionally made chicken…”
Section: Discussionmentioning
confidence: 99%